Deconstructing Dawson's Creek - Boborol, Theodore C.
This thesis is a textual analysis of the youth drama series Dawson's Creek. Deconstruction, a kind of textual analysis, is used. The research looked into the values on human relationships, family and friendship, produced by Dawson's Creek. In doing so, the research made use of the theories of semiotics and post-structuralism. By analysing 13 episodes of the series' first two seasons, it was found that Dawson's Creek presents some subversive values in its texts. Overall, however, the series still preserves traditional values on human relationships. Traditional values in the research mean the researcher's perceived traditional or Filipino values.